Transcriptome Analysis of the Molecular Patterns of Pear Plants Infected by Two Colletotrichum fructicola Pathogenic Strains Causing Contrasting Sets of Leaf Symptoms - Fu, Min; Bai, Qing; Zhang, Hui; Guo, Yashuang; Peng, Yuhong; Zhang, Pengfei; Shen, Liang; Hong, Ni; Xu, Wenxing; Wang, Guoping (Frontiers in Plant Science, 2022)
Colletotrichum fructicola infects pear leaves, resulting in two major symptoms: tiny black spots (TS) followed by severe early defoliation and big necrotic lesions (BnL) without apparent damage depending on the pathotypes. How the same fungal species causes different symptoms remains unclear. To understand the molecular mechanism underlying the resulting diseases and the diverse symptoms, two C. fructicola pathogenetic strains (PAFQ31 and PAFQ32 responsible for TS and BnL symptoms, respectively) were inoculated on Pyrus pyrifolia leaves and subjected to transcriptome sequencing at quiescent stage (QS) and necrotrophic stage (NS), respectively. In planta, the genes involved in the salicylic acid (SA) signalling pathway were up-regulated at NS caused by the infection of each strain. In contrast, ethylene, abscisic acid (ABA), and jasmonic acid (JA) signalling pathways were specifically related to the TS symptoms caused by the infection of strain PAFQ31, corresponding to the yellowish and early defoliation symptoms triggered by the strain infection. Correspondingly, SA was accumulated in similar levels in the leaves infected by each strain at NS, but JA was significantly higher in the PAFQ31-infected as measured using high-performance liquid chromatography. Weighted gene co-expression network analysis also reveals specific genes, pathways, phytohormones, and transcription factors (TFs) associated with the PAFQ31-associated early defoliation. Taken together, these data suggest that specific metabolic pathways were regulated in P. pyrifolia in response to the infection of two C. fructicola pathotypes resulting in the diverse symptoms: JA, ethylene, and ABA accumulated in the PAFQ31-infected leaves, which negatively affected the chlorophyll metabolism and photosynthesis pathways while positively affected the expression of senescence-associated TFs and genes, resulting in leaf yellowing and defoliation; whereas SA inhibited JA-induced gene expression in the PAFQ32-infected leaves, which led to hypersensitive response-like reaction and BnL symptoms.